Solar powered portable handphone charger / Mohd Saiful Najib Ismail @ Marzuki - Ismail @ Marzuki, Mohd Saiful Najib (2010)
This project is about to develop a Portable Handphone Charger that creates an output to charge a hand phone. The Portable Handphone Charger consist of four main parts, that is solar panel, charger controller circuit, storage device (rechargeable battery) and cigarette plug for output port. Generally, Portable. Handphone Charger project focuses on the theories, designs, programming and performs a monitoring on voltages, current and control the excessive limit of the battery.